2017
DOI: 10.4236/abb.2017.811030
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment and Potential Anti-Inflammatory Effect of Ethanolic Extract of <i>Syzygium aromaticum</i> in Albino Rats

Abstract: The present study was undertaken to investigate the effect of the ethanolic extract of Syzygium aromaticum to albino rats. Forty eight Albino rats were employed to test the safety and the anti-inflammatory effect of the extract. Safety of the extract was examined on experimental animal's model at three dose levels of the extract orally in daily doses for three weeks. Effects of S. aromaticum on rats revealed no significant effect on biochemical or haematological parameters. The anti-inflammatory effect of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…Kazi et al (2017) also used CLP at 1 g/kg and observed no effects on AST, ALT, and ALP activity in rabbits. Moreover, the actions of AST and ALT showed no significant differences for all treatments in rats fed clove extract at 250 and 500 mg/kg diet (Saeed et al, 2017). In another study, Mustafa (2016) showed no significant differences in AST, ALT, and ALP enzyme concentrations in broiler chickens fed mixed essential oils (cloves, anise, and caraway) at a rate of 200, 400, and 600 mg/kg feed.…”
Section: Resultsmentioning
confidence: 94%
“…Kazi et al (2017) also used CLP at 1 g/kg and observed no effects on AST, ALT, and ALP activity in rabbits. Moreover, the actions of AST and ALT showed no significant differences for all treatments in rats fed clove extract at 250 and 500 mg/kg diet (Saeed et al, 2017). In another study, Mustafa (2016) showed no significant differences in AST, ALT, and ALP enzyme concentrations in broiler chickens fed mixed essential oils (cloves, anise, and caraway) at a rate of 200, 400, and 600 mg/kg feed.…”
Section: Resultsmentioning
confidence: 94%
“…Antiinflammatory activity of clove oil was studied in mice at a dose of 33 mg/kg body weight intraperitoneal in which clove oil significantly suppressed the increase paw thickness by 50.6 % compared with control mice at 3 h (Taher et al, 2015). Similarly, anti-inflammatory effect of ethanolic extract of S. aromaticum in carrageenan-induced paw edema in rats has been reported with significant decrease in the edema at efficacy rates of 79.41, 82.39 and 63.92 % at the dose of 500 mg/kg body weight at 2 nd , 4 th and 6 th h, respectively (Saeed et al, 2017). Nikoui et al (2017) studied the anti-inflammatory effect of clove oil in thirty adult male dogs which were divided into four groups after surgical incision on abdomen.…”
Section: Discussionmentioning
confidence: 71%
“…Various studies have proven the antimicrobial, antioxidant, anti-inflammatory, and anti-cancer effects of S. aromaticum. Anti-inflammatory effect of the alcoholic extract of oral S. aromaticum has been proven in animal studies without reported side effects (21). In a study, it was found that clove oil cream was effective in wound healing and decreasing sphincter pressure of the anus (22).…”
Section: Discussionmentioning
confidence: 99%